THE ROLE OF SOCIAL SUPPORT ON TREATMENT ADHERENCE IN TB PATIENTS: A SYSTEMATIC REVIEW - Ardila Lailatul Barik; Retno Indarwati; Sulistiawati Sulistiawati (Nurse and Health: Jurnal Keperawatan, 2020)
Background: Adherence to treatment regimens in TB patients was carried out by using a pharmacological and non-pharmacological approach or paying attention to the social aspects of the patient.Objective: This review is to analyze and identify the literature related to the social support approach to treatment adherence in TB patients.Design: The systematic design of this review is to find and review journal articles from the database using Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA).Data Sources: This systematic review is based on literature studies from various journal data bases in the last 5 years, including Scopus, ScienceDirect, ProQuest and Google Scholar by conducting a comprehensive review. The keywords in this Systematic review are adjusted to the Medical Subject Heading (MeSH) and use a combination of Boolean operators (AND and OR), namely "Social Support" OR "Family Support" OR "Peer Group Support" OR "Nurse Support" AND "adherence OR Compliance" AND "Tuberculosis" OR "pulmonary TB”.Review Methods: The review method on this systematic review uses the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Evaluation) guidelines and the assessment of the quality of the study in the article uses the JBI critical appraisal tools.Results: In this literature ten articles fit the inclusion and exclusion criteria and relate to the topic. It was found that social support which includes family support, peer support and support from health workers is one of the driving factors for treatment adherence in TB patients.Conclusion: Aspects of social support which include family support, peer group support and support from health workers have an important role and become a driving factor for TB patients to adhere to the treatment regimen. For further research, the development of interventions to improve adherence to TB patients needs to consider these social aspects. Keywords: Medication Adherence, Social Support, Tuberculosis.